The Strategic Analysis of Singapore`s Brand and Rebrand Campaigns - Răzvan-Andrei CORBOŞ (Revista de Management Comparat International)
“Uniquely Singapore” and “YourSingapore”! Brand and rebrand! 2004 and 2010! From the economic point of view Singapore has grown exponentially in the last half century. The beginning of the third millennium has brought the need of finding new sources of growth by correctly identifying the opportunities that the competitive environment has to offer. Thus, a branding campaign was born in order to present Singapore as a unique tourist destination: a dynamic state, rich in contrasts and colors, offering a mix of culture, art, architecture and cuisine in a unique blend of modernity and tradition. Even if in 2009 the effects of the economic and financial crisis temporarily limited the upward trend of the campaign’s positive effects, the Singapore authorities found new tools to improve the country’s brand by adapting to new digital media, promotion through events and directmarketing aggressively. The paper analyses how the campaigns were created and applied branding / rebranding of the city-state of Singapore in 2004 and 2010, as well as the economic effects of these efforts that have proved successful.